The Influence of Religiosity and Spirituality Towards Students’ Psychological Well-Being During Covid-19 Pandemic - Supriatna, Ecep; Septian, Muhammad Rezza (Jurnal Pendidikan Islam, 2021)
This article aims to examine the influence of religiosity and spirituality on the students' psychological well-being during the Covid-19 pandemic. The method used is a relational survey method. The participants of this research were 627 students who studied in universities located in Bandung and Cimahi. The universities included State Islamic University of Sunan Gunung Djati Bandung, the Indonesian Education University, Jenderal Ahmad Yani University, and the Siliwangi Institute of Teacher Training and Education. The data were collected using a questionnaire instrument consisting of a questionnaire of religiosity, spirituality, and psychological well-being. The results showed that both religiosity and spirituality had an effect on psychological well-being. It is shown that religiosity had a higher effect than spirituality on students' psychological well-being during the Covid-19 pandemic. Â